Could Emotions Be Beneficial for Interaction Quality Modelling in Human-Human Conversations? - Spirina, Anastasiia; Minker, Wolfgang; Sidorov, Maxim (Text, Speech, and Dialogue, 2017)
There are different metrics which are used in call centres or Spoken Dialogue Systems (SDSs) as an indicator for problem detection during the dialogue. One of such metrics is emotional state. The measurements of emotions can be a powerful indicator in different task-oriented services. Besides emotional state, there is another widely used metric: customer satisfaction (CS), which has a modification called Interaction Quality (IQ). The both models of CS and IQ may include emotional state as a feature. However, is it an actually necessary feature? Some users/customers can be very emotional, while other can be insufficiently emotional in different satisfaction categories. That is why emotional state may be not an informative feature for IQ/CS modelling. Our research is dedicated to the definition of the emotions measurements role in IQ modelling task.